Glomus rubiforme, an arbuscular mycorrhizal fungus new to the mycota of Poland - Janusz Błaszkowski; Tadeusz Madej; Mariusz Tadych (Acta Mycologica, 2014)
Glomus rubiforme is described and illustrated. as well as its occurrence in Poland and in the world is presented. Glomus rubiforme forms pale yellow to light brown spores arranged in blackberry-like sporocarps. The spores develop from a centrally positioned, inflated, thick-walled cell. The spore wall consists of two layers: a sloughing, hyaline outer layer adherent to a coloured, laminated layer. Glomus rubiforme is a new arbuscular mycorrhizal fungus to the mycota of Poland.